Access to New Endoperoxide Derivatives by Electrochemical Oxidation of Substituted 3‐Azabicyclo[4.1.0]hept‐4‐enes. Issue 14 (20th February 2015) - Nuter, Frédérick; Dimé, Abdou Khadre Djily; Chen, Cheng; Bounaadja, Lotfi; Mouray, Elisabeth; Florent, Isabelle; Six, Yvan; Buriez, Olivier; Marinetti, Angela; Voituriez, Arnaud
Abstract A series of substituted 3‐azabicyclo[4.1.0]hept‐4‐ene derivatives were prepared and analysed by cyclic voltammetry. Preparative aerobic electrochemical oxidation reactions were then carried out. Three original endoperoxides were isolated, characterised and subjected to antimalarial and cytotoxicity activity assays.